Faktor Dominan Yang Menyebabkan Perilaku Merokok Pada Remaja Di Smk Taruna Jaya Prawira (TJP) Tuban - Jasmine, Melinda Margareth; Yunariyah, Binti; Jannah, Roudlotul (Peneliti.net, 2024)
Smoking is a big problem for public health. Apart from a health perspective, smoking can also affect the personality of the smoker himself. People's smoking behavior from year to year shows an increasing trend. This happens not only because of the behavior of adults but has spread among teenagers and also children. The number of teenage smokers has been getting higher in the last 5 years, starting from 18.3% to 19.2%. The purpose of this study was to determine the dominant factors that cause smoking behavior in adolescents at SMK Taruna Jaya Prawira. Descriptive research design with a cross-sectional approach. The study population was all students of SMK Taruna Jaya Prawira (TJP) Tuban class X, Department of Light Vehicle Engineering (TKR) for the 2022/2023 academic year, totaling 171 people, with a sample size of 120 people. The sampling technique used is Simple Random Sampling. The research variable is the dominant factor that causes smoking behavior in adolescents. How to collect data by distributing questionnaires and then processing the data. The results showed that most of the adolescents (57.5%) did not smoke and almost half of them smoked (42.5%). And from the results of research on adolescents who smoke, it is found that the factors that can cause smoking behavior in adolescents are the influence of friends with a frequency (72.5%). This shows that early adolescence can be influenced by the attachments around them. Teenagers tend to imitate the behavior of their friends so when their friends smoke, they have the potential to imitate them. Therefore for respondents to consider and choose their peers and the environment in which they can grow, and are motivated to carry out better activities in the future